The Effect of ESG (Environmental, Social, Governance) Disclosure on Audit Quality with Firm Size and Industry Complexity as Moderating Variables (An Empirical Study on Manufacturing Companies Listed On the IDX in 2020–2024) - Marsel Pasaribu; Ricky Agusiady; Fitriana Fitriana (LPPM Institut Pendidikan Nusantara Global, 2026)
Weak or non-transparent ESG reports regarding governance structure and internal control policies can signal to auditors a high inherent risk of control failure, which in turn increases the risk of material misstatement due to fraud. This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on audit quality, as well as the effect of company size and industry complexity as moderating variables in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024. The research sample was determined using purposive sampling. The study uses a causal associative method with a quantitative approach and panel data regression analysis. The statistical data processing and analysis were carried out using STATA statistical software. The results showed that disclosure of environmental aspects had no effect on audit quality. In contrast, social and governance aspects have a negative effect on audit quality. This finding indicates that the higher the social and governance score of a company, the auditor tends to consider the audit risk lower, thus reducing the need for additional independent audits. Simultaneously, social and governance are also proven to reduce audit quality. Firm size is not shown to moderate the relationship between ESG and audit quality, as both large and small firms may experience an exaggerated perception of high ESG reputation. However, industry complexity is shown to positively moderate the relationship between social and governance aspects and audit quality. In complex industries, despite high ESG scores, the demand for rigorous audit oversight still increases due to the high potential reporting risks. This study provides an empirical contribution in understanding the dynamics of ESG influence on audit in Indonesia's manufacturing sector, and suggests the importance of considering operational complexity factors in designing an effective audit oversight system.